2001
DOI: 10.1055/s-2001-9715
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Aldol Reaction of Trimethoxysilyl Enol Ethers with Aldehydes Catalyzed by p-Tol-BINAP · AgF Complex

Abstract: New catalytic asymmetric Mukaiyama-type aldol reaction using trimethoxysilyl enol ethers was achieved using p-Tol-BINAP·AgF complex as a catalyst. High syn-and enantioselectivities were obtained both from the E-and Z-silyl enol ethers.The Mukaiyama aldol reaction is a favorite method for the synthesis of b-hydroxy carbonyl compounds. 1 Although a variety of chiral Lewis acid catalysts have been developed for the asymmetric reaction of trialkylsilyl enol ethers or ketene trialkylsilyl acetals with carbonyl comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(11 citation statements)
references
References 3 publications
1
9
0
1
Order By: Relevance
“…Catalysts derived from complexes prepared with metals such as lead, (243) silver, (244,245) platinum, (143) and lanthanides (246) mediate catalytic, enantioselective propionate aldol addition reactions. The addition of propiophenone to benzaldehyde mediated by a praseodynium complex prepared with a chiral macrocyclic ether is noteworthy, as it is a rare example of the use of a lanthanide in such aldol addition reactions and constitutes the successful use of a macrocyclic ligand (Eq.…”
Section: Enoxysilanes and Stannanesmentioning
confidence: 99%
See 1 more Smart Citation
“…Catalysts derived from complexes prepared with metals such as lead, (243) silver, (244,245) platinum, (143) and lanthanides (246) mediate catalytic, enantioselective propionate aldol addition reactions. The addition of propiophenone to benzaldehyde mediated by a praseodynium complex prepared with a chiral macrocyclic ether is noteworthy, as it is a rare example of the use of a lanthanide in such aldol addition reactions and constitutes the successful use of a macrocyclic ligand (Eq.…”
Section: Enoxysilanes and Stannanesmentioning
confidence: 99%
“…The reaction prescribes the use of 20 mol% catalyst, furnishing adducts in up to 95% ee. Simple chiral bisphosphine silver(I) complexes catalyze enantioselective addition reactions of stannyl enolates, (244) trimethoxysilyl enolates, (245) and diketene (247) with aldehydes. Under typical conditions, the addition reaction is catalyzed by 5-10 mol% of silver-BINAP complexes at -20°.…”
Section: Enoxysilanes and Stannanesmentioning
confidence: 99%
“…This unique character of ScF 3 denoted that its reactivity toward TMS and DMS enolates was different from that of conventional Lewis acid or fluoride ion63 (Lewis base)-catalyzed reactions. Some reports have shown that fluoride ions can activate silicon enolates effectively even in a protic solvent 64. The detailed mechanism of the preferential activation of DMS enolates by ScF 3 remains unknown.…”
Section: Lewis-base Catalysis In Aqueous or Organic Solventsmentioning
confidence: 99%
“…Some reports have shown that fluoride ions can activate silicon enolates effectively even in a protic solvent. 64 The detailed mechanism of the preferential activation of DMS enolates by ScF 3 remains unknown.…”
Section: Lewis-base Catalysis In Aqueous or Organic Solventsmentioning
confidence: 99%
“…Am besten wurden durch Silber(I)‐ oder Kupfer(I)‐fluorid katalysierte Aldolreaktionen untersucht. Yamamoto und Mitarbeiter beobachteten bei der Addition von Trialkoxysilylenolethern an aromatische und α,β‐ungesättigte Aldehyde in Gegenwart des p ‐Tol‐Binap‐AgF‐Komplexes 346 hohe Enantioselektivitäten, wenn die Reaktion in einem protischen Solvens wie Methanol ausgeführt wurde (Schema ) 380d. Yamagishi und Mitarbeiter erhielten mit anderen Silbersalzen, darunter Acetaten und Tetrafluoroboraten, ebenfalls die gewünschten Aldolprodukte, allerdings mit niedrigeren Enantioselektivitäten 380e–f.…”
Section: Difunktionelle Katalyse: Stereokartographie354unclassified